Analisis Efektivitas-Biaya Antihipertensi Amlodipin Dibandingkan Candesartan Pada Pasien Stroke Iskemik Rawat Jalan di Rumah Sakit Surakarta - Lestari, Rizkia Putri; Andayani , Tri Murti; Rahmawati , Ismi (Universitas Borneo Lestari, 2026)
Hypertension is one of the risk factor for ischemic stroke. Amlodipin and Candesartan are hypertensive therapies in stroke patients. The use of antihypertensive drugs requires long-term treatment, so it is necessary to conduct a cost-effectiveness analysis to determine effective and efficient use of drugs. The purpose of this study is to find out the most cost-saving antihypertensive at Hospital Surakarta. The study was conducted retrospectively on outpatient ischemic stroke patients at the Surakarta Regional General Hospital for the periode 2023-2024. Sample number data used was 114 on ischemic stroke patients according to the inclusion criteria. Effectiveness is seen from the patient's blood pressure reaching the target and the cost is calculated from the provider's perspective, including direct medical costs. CEA is calculated based on the value of ACER and ICER. The results showed the effectiveness of Amlodipin 66,10% and Candesartan 54,55%. The average total cost of Amlodipin is Rp. 556,129 ± 208,187 and Rp. 620,436 ± 232,382 for Candesartan. The value of ACER for amlodipine was Rp. 8,413.44, while candesartan is Rp. 11,377.32. The calculation of the ICER value obtained a negative result Rp. 5,584. The results of the cost-effectiveness analysis showed that amlodipin is a cost-saving antihypertensive for outpatient ischemic stroke patients.